Pertanggungjawaban Coercive Services oleh Private Military and Security Company dalam Konflik Bersenjata - Dwiki Nurcahyo Nugroho; Ayub Torry Satriyo Kusumo (Faculty of Law Universitas Sebelas Maret, 2019)
This research aims at two things. First, describes and analyzes the legal standing of Private Military and Security Company (PMSC) in International Humanitarian Law. Second, analyzes the responsibility mechanism for Private Military and Security Company (PMSC) personnel. This research is normative legal research viewed from applied prescriptive. The legal material used by this research include primary and secondary legal material. The legal material was collected by library research and analyzed by deductive methods. The results show that PMSC cannot be equated with mercenaries as regulated in Article 47 Additional Protocol I Geneva Convention 1977. According to Montreux Document, the legal standing of PMSC will depend on the signed contract. Montreux Document provisions explain that PMSCs status can be civilians, members accompanying armed forces, and illegal combatants. The coercive services responsibility conducted by PMSC personnel will also depend on the agreement made by the parties. PMSC personnel will be individually responsible when the conduct is not representing the contracting subject.